Immunomodulatory effects of laser-synthesized nanodiamonds on peripheral blood mononuclear cells: evaluation of unconjugated, PEGylated, and antibody-conjugated formulations - Alexander, Elena; Leong, Kam W. (Frontiers in Nanotechnology, 2024)
The application of laser-synthesized nanodiamonds (LNDs) is of great interest to biomedical researchers and drug developers because this emerging method of synthesis yields nanodiamonds of consistent size (< 5 nm diameter) and surface chemistry that can be functionalized to perform a staggering range of highly specialized tasks. The present study assessed the threshold at which LNDs in various conjugations and concentrations triggered immune responses and cytotoxicity in peripheral mononuclear blood cells from healthy donors, as assessed by changes in ATP concentrations and induced secretion of the cytokines IFN-γ, IL-6 and TNF-α. Conjugations assessed were raw (unconjugated) NDs, PEGylated (PEG5k-NDs), and antibody conjugated to goat anti-mouse antibodies (IgG-NDs). Concentrations of each conjugation were prepared and tested at 50.0, 10.0, 2.0, 0.4, and 0.08 µg/ml. Results showed that pegylated and raw NDs were well tolerated, with the indicators of inflammation or minimal cytotoxicity emerging only at the highest concentrations tested (50.0 µg/ml). IgG-NDs showed signs of inflammatory responses at the two highest concentrations tested (10.0 and 50.0 µg/ml). There was some evidence that the dilutant vehicle used for ND suspension may have contributed to the immune response. All three ND configurations increased ATP concentration in a dose-dependent manner, up to a concentration of 10.0 µg/ml. At the highest concentration (50.0 µg/ml), the ND solutions showed minimal signs of cytotoxicity. Conclusions from this testing suggest that LNDs are likely to offer substantial utility in biomedical applications because of their capacity to evade the immune response at concentrations at least as high as 2.0 µg/ml and potentially up to 50.0 µg/ml.